Goal-Free Evaluation Approach Instrument Focused on the Numeracy Skills of Grade IV Students at a Sekolah Penggerak in Singaraja City - Ketut Ari Sukra Darma; I Wayan Widiana; Gede Wira Bayu (MIMBAR PGSD Undiksha, 2025)
This study was motivated by the low numeracy skills of students in elementary school, as well as the use of evaluation instruments that was not yet optimal. This research aims to analyze the validity and practicality of evaluation instruments using a goal free evaluation approach.  The research uses a 4D model (Define, Design, Development, Disseminate). This study takes the subject of evaluation instruments, while the object is the validity of basic education content, evaluation content, teacher and student responses. Data collection methods are quantitative observation and questionnaires. Instruments for collecting data are observation guidelines, rating scale sheets, interview guidelines, and questionnaires. The results of the research show that: (1) the validity results of basic education experts obtained a validity index of 1 with high content qualifications, (2) the validity results of evaluation experts obtained a validity index of 0.96667 with high content qualifications, (3) the achievement level of teachers' responses to the instrument was 90% and 100% with very good qualifications, (4), the achievement level of student responses to the instrument was 90.77% and 96.17% with very good qualifications, so that the evaluation instrument using the goal free evaluation approach is effective in improving Numeracy ability of fourth grade elementary school students. The implication of this research is that the instrument helps evaluate student numeracy objectively, improve learning and educational decision making.